An Analysis of Tourist Satisfaction with Attractions at Saung Angklung Udjo - Saripah, Silqy Lailatul; Noor, Any Ariani; Chendraningrum, Dinarsiah (Journal of Tourism Sustainability, 2024)
This study analyzes tourist satisfaction with tourist attractions at Saung Angklung Udjo. The research method used is a quantitative method with a questionnaire instrument. The population in this study were tourists visiting Saung Angklung Udjo, with a sample of 114 respondents selected using a purposive sampling technique. The results showed that tourists were satisfied with the attractions at Saung Angklung Udjo. This is influenced by aspects such as activities, amenities, and accessibility, which are provided. Saung Angklung Udjo has provided an interesting experience for tourists through typical angklung performances from various activities, adequate supporting service facilities, and ease of accessibility, providing comfort for tourists. The research findings also reveal tourists' opinions on suggestions for future attractions at Saung Angklung Udjo, such as increasing the variety of themes and concepts of the show and improving the tour's cleanliness and safety. This research provides implications for managers to continue to improve the quality and innovation of tourist attractions, and the results are expected to be material for evaluation and input for Saung Angklung Udjo managers in increasing tourist satisfaction in the future.